Formulasi Kebijakan Undang - Undang Tindak Pidana Kekerasan Seksual - Sintia Kartini Haniandaresta; Izzatusholekha Izzatusholekha (Lembaga Pengembangan Kinerja Dosen, 2024)
This undergraduate thesis is talking about the formulation of the draft law on the elimination of sexual violence in the People's Legislative Assembly of the Republic of Indonesia. The increasing number of cases of sexual violence every year, so that Komnas Perempuan proposed to the House of Representatives to make a law to deal with it. The purpose of this study is to analyze how the policy formulation of the draft law on the elimination of sexual violence in the People's Representative Council of the Republic of Indonesia is. The research method used is descriptive qualitative. The theory used in this study is based on Willia Dunn's theory (2000: 226) which has 4 indicators, namely the first indicator of problem finding, the second indicator of problem definition, the third indicator of problem specification, and the fourth indicator of problem recognition. The results of the research at the problem-finding stage carried out by the DPR on the first indicator of problem-finding can be said to be perfect because it involves all stakeholders, on the second indicator the problem definition carried out by the DPR has been carried out according to the policy formulation stage by clustering problems, on the third indicator the problem specifications are carried out by the DPR namely by holding a meeting again related to the points that should be regulated in the PKS Bill so that it overcomes sexual violence in Indonesia effectively and comprehensively, in the final stage, namely recognizing the problem, the DPR has not carried out these indicators so that the initial goal of forming the law did not work. effectively.